The Influencee of Competence and Independence on the Audit Quality of the Inspectorate of the National Narcotics Agency of the Republic of Indonesia - Noorina Hartati; Anton Robiansyah (Journal of Economics, Business, and Government Challenges, 2021)
The purpose of this study is to provide empirical evidence about the influence of competence and independence on audit quality. The objects of this research were the auditors who work at the inspectorate of the National Narcotics Agency of the Republic of Indonesia. The data used in this study were primary data in form of questionnaires which distributed to auditors at the Inspectorate of Bengkulu Province. The number of questionnaires which distributed was 48 questionnaires. Some data were analyzed using multiple linear regression analysis with the SPSS 18 program. The results of hypothesis test showed that the competence and independence had a positive and significant influence on the quality of the inspectorate of the National Narcotics Agency of the Republic of Indonesia. The results of the study supported the theory of expectations and the previous research which showed that competence had a positive effect on audit quality because the higher the increase in competence, the higher the audit quality, and the independence brought a positive effect on audit quality because the higher the independence of auditors in BNN inspectorate of the Republic of Indonesia, it made the auditors had better performance so that it would improve the audit quality.